2021
DOI: 10.3389/fmolb.2021.747650
|View full text |Cite
|
Sign up to set email alerts
|

Activity of PD-1 Inhibitor Combined With Anti-Angiogenic Therapy in Advanced Sarcoma: A Single-Center Retrospective Analysis

Abstract: Background: Immune checkpoint inhibitors (ICIs) are employed to treat various cancers, including soft tissue sarcomas (STSs), and less than 20% of patients benefit from this treatment. Vascular endothelial growth factor (VEGF) promotes the immunosuppressive tumor microenvironment and contributes to ICI-resistant therapy. Anti-VEGF receptor tyrosine-kinase inhibitors (TKIs) combined with ICIs have shown antitumor activity in patients with alveolar soft-part sarcoma (ASPS). However, they have not been extensivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The SARC028 study reported 20% (2/10) ORR to pembrolizumab monotherapy in patients with DDLPS 4 . Correlative analyses of the SARC028 trial revealed an association between immune infiltrate and response to pembrolizumab in DDLPS 18 . In a retrospective study from China, 36.3% (4/11) of patients with DDLPS showed an objective response to AIs plus ICIs combination therapy 19 .…”
Section: Discussionmentioning
confidence: 97%
“…The SARC028 study reported 20% (2/10) ORR to pembrolizumab monotherapy in patients with DDLPS 4 . Correlative analyses of the SARC028 trial revealed an association between immune infiltrate and response to pembrolizumab in DDLPS 18 . In a retrospective study from China, 36.3% (4/11) of patients with DDLPS showed an objective response to AIs plus ICIs combination therapy 19 .…”
Section: Discussionmentioning
confidence: 97%
“… 26 Anlotinib combined with pd-1 antibody also reported in STSs recently. In a single-center retrospective analysis, 27 61 advanced STS patients were treated with ICIs alone or combined with TKIs, the median PFS was significantly prolonged after ICI treatment in combination with TKIs (11.74 months) compared to ICI treatment alone (6.81 months), with a 12-month PFS rate of 42.9% and overall response rate of 30% in ICI-TKI combination group. We speculate that anlotinib combined with pd-1 inhibitors can play a synergistic role in the treatment of LMS, which still needs to be confirmed by relevant clinical and basic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Only 1 PR and 1 minor response (decrease in the size of the target lesion of less than 30%) were observed in these 6 patients ( 15 ). A retrospective study, which included 20 LMS patients among 61 who received PD-1 and TKIs, suggested that LMS patients had the lowest response rate compared with other subtypes, and rapid progression could occur if PD-1 monotherapy was administered ( 16 ). As for PD-1 combination chemotherapy, a phase II study recruiting 15 LMS patients among 57 patients who received intravenous pembrolizumab and oral cyclophosphamide reported that the 6-month non-progression rate was 0% for LMS, but we considered the efficacy of this result limited as oral cyclophosphamide is not a standard regimen for LMS ( 17 ).…”
Section: Discussionmentioning
confidence: 99%